Contrast-Enhanced Ultrasound Findings of Hepatocellular Carcinoma With Neuroendocrine Carcinoma: A Case Report - Wang, Hong; Yang, Dan; Wu, Zhenru; Luo, Yan; Ling, Wenwu (Frontiers in Medicine, 2021)
Background: Hepatocellular carcinoma (HCC) with the concurrent occurrence of primary hepatic neuroendocrine carcinoma (NEC) of the liver is very rare. Preoperative diagnosis of hepatocellular carcinoma with neuroendocrine carcinoma to be very difﬁcult. Case presentation: A 33-year-old male was referred to our hospital due to liver space-occupying lesions. To further diagnose, he received laboratory tests, gray-scale US, and contrast-enhanced ultrasound (CEUS). In this present study, ethical approval was not necessary, as this article is a case report, which is based on the clinical information of the patient. The patient gave his permission for publication of the case. A gray-scale abdominal ultrasound image demonstrated a mass at the inferior segment of the right posterior liver lobe with liver cirrhosis. In CEUS, the lesion was homogeneously hyper-enhanced in the arterial phase, heterogenous mild enhancement in the portal phase, and hypo-enhanced in the parenchymal phase. The patient received middle hepatectomy, splenectomy, and cholecystectomy. He had an uneventful recovery from the procedure. Conclusions: We presented a case report with HCC with NEC, focusing on the ultrasound imaging features of this tumor, especially its enhancement pattern on CEUS. This is the first CEUS performance reported in association with HCC with NEC. CEUS provided helpful information for diagnosis. We should not simply diagnose such tumors as HCC, but think about the possibilities of HCC another type of cancer, especially in patients with chronic liver disease.